Preparation and Characterization of Spherical Crystals of Simvastatin To Enhance The Solubility and Micrometric Properties - Janrao, Kunal K.; Gadhave, M V; Banerjee, S K; Gaikwad, D D (Asian Journal of Pharmaceutical Research and Development, 2014)
Simvastatin is an Antihyperlipidemic commonly used in the treatment of hypercholesterolemia and dyslipidemia. Due to low solubility in water and poor micrometric properties of Simvastatin leads to low dissolution rate. The aim of present investigation was to improve solubility, dissolution rate and enhancement of micromeritic properties of the poorly solvable drug. The parameters optimized were type, extent, and method of addition of bridging agent. The spherical agglomerate/crystals of Simvastatin were prepared by solvent change method in the presence of hydrophilic polymer in different concentration. The solvent system used was Ethanol, water and chloroform as good solvent, antisolvent and bridging liquid respectively. Spherical agglomerates were subjected for determination of percent drug content and particle size analysis. The agglomerates were also characterized by Differential Scanning Calorimetry (DSC), Fourier Transform Infrared Spectroscopy (FTIR), X-ray Powder Diffraction (XRD) and Scanning Electron Microscopy (SEM) analysis. The FTIR and DSC study showed no interaction between drug and polymer. XRD studies showed a slight decrease in crystallinity in agglomerates. Spherical agglomerates showed improvement in solubility, dissolution rate and micromeritic properties in comparison to that of the pure drug. The SEM also showed that the agglomerate possess a good spherical shape.